2015
DOI: 10.1149/06916.0011ecst
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Engineering to Improve Ionic Conduction in Thin Films for Micro-SOFCs

Abstract: New emerging disciplines are specifically devoted to study trivial and non-trivial effects resulting from working in the nanoscale, however, the implementation of these nanostructures in real devices is still a major challenge. Thin film deposition and silicon microtechnology is probably the most promising and straightforward combination for the reliable integration of nanomaterials in real devices. In particular, the implementation of pure ionic and mixed ionic/electronic conductors (MIECs) in thin film form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the samples studied in the present work, the activation energies scattered from 0.5 to 0.6 eV. This could probably be related to the polycrystalline (nanocrystalline) structure of the investigated YSZ films so that the oxygen ions can move along the grain boundaries [26,27]. Earlier, High Resolution Transmission Electron Microscopy studies demonstrated the YSZ films in the investigated stacks to have a nanocrystalline structure with the average grain sizes ≈40 nm (in the 40 nm thick YSZ films); the grain boundaries were perpendicular to the substrate [12].…”
Section: Resultsmentioning
confidence: 73%
“…In the samples studied in the present work, the activation energies scattered from 0.5 to 0.6 eV. This could probably be related to the polycrystalline (nanocrystalline) structure of the investigated YSZ films so that the oxygen ions can move along the grain boundaries [26,27]. Earlier, High Resolution Transmission Electron Microscopy studies demonstrated the YSZ films in the investigated stacks to have a nanocrystalline structure with the average grain sizes ≈40 nm (in the 40 nm thick YSZ films); the grain boundaries were perpendicular to the substrate [12].…”
Section: Resultsmentioning
confidence: 73%